IMPLEMENTASI GEMINI AI DALAM PENGEMBANGAN APLIKASI E-COMMERCE MOBILE GENERATE DESKRIPSI PRODUK - Handoko, Rifky Mustaqim Handoko; Wahyuni Putra; Ryan Delon Pratama; Nova Noor Kamalasari; Viktor Handrianus Pranatawijaya (Universitas Serang Raya, 2024)
Abstract— In the rapidly evolving digital era, e-commerce has become a crucial industry for effectively reaching consumers. This articlediscusses the implementation of artificial intelligence (AI) technology, specifically Gemini AI, in developing a mobile e-commerce applicationusing Flutter SDK. AI technology is utilized to automatically generate product descriptions based on user selections, enhancing efficiency anduser experience. The integration of Gemini AI API enables the application to provide informative and engaging product information. Theresearch findings indicate that the use of AI technology in e-commerce can add value in effectively and efficiently presenting productinformation to users, providing recommendations for the future development of e-commerce applications.Keywords— Artificial Intelligence, Product Description, Mobile, Flutter, Gemini